An exploration of L2 listening problems and their causes - Gao, Liping (2014)
Listening has long been recognised as the most challenging skill for teachers, students and researchers working in the context of L2 English. However, it has also been the least researched of the four language skills, and one that has received the least attention in second language acquisition.